Pengetahuan Ibu Hamil Terhadap Sikap Ibu Hamil Dalam Tes HIV Di Pusat Kesehatan MAsyarakat Sikumana Tahun 2016 - NI LUH MADE DIAH PUTRI ANGGARAENINGSIH (JURNAL INFO KESEHATAN, 2017)
Emotional control is an attempt to reduce emotions to hide or suppress perceived emotions. The deep breathing relaxation technique is believed to help lower the tension and provide calm by stimulating the body releasing Endorphin hormones that can strengthen the immune system, keep brain cells young, fight against, decrease aggressiveness in human relationships, boost spirits, endurance, and creativity. The purpose of the study was to identify the effect of deep breathing relaxation techniques on emotional control in patients with tuberculosis at the Community Lung Health Center (BKPM) Magelang. The research method used quasi-experiment with One Group pre-test-post-test research design without a control group with sample number 29 respondents. The inner breathing duration is done once a week for 4 weeks. The results obtained in this study is that there is a significant difference mean of emotional control before and after deep breathing relaxation with value p = <0.001. The conclusion of this research is the effect of deep breath relaxation on the control of emotion in TB patient in BKPM Magelang.